Vitamin B6 Metabolism Determines T Cell Anti-Tumor Responses - Bargiela, David; Cunha, Pedro P.; Veliça, Pedro; Foskolou, Iosifina P.; Barbieri, Laura; Rundqvist, Helene; Johnson, Randall S. (Frontiers in Immunology, 2022)
Targeting T cell metabolism is an established method of immunomodulation. Following activation, T cells engage distinct metabolic programs leading to the uptake and processing of nutrients that determine cell proliferation and differentiation. Redirection of T cell fate by modulation of these metabolic programs has been shown to boost or suppress immune responses in vitro and in vivo. Using publicly available T cell transcriptomic and proteomic datasets we identified vitamin B6-dependent transaminases as key metabolic enzymes driving T cell activation and differentiation. Inhibition of vitamin B6 metabolism using the pyridoxal 5’-phosphate (PLP) inhibitor, aminoxyacetic acid (AOA), suppresses CD8+ T cell proliferation and effector differentiation in a dose-dependent manner. We show that pyridoxal phosphate phosphatase (PDXP), a negative regulator of intracellular vitamin B6 levels, is under the control of the hypoxia-inducible transcription factor (HIF1), a central driver of T cell metabolism. Furthermore, by adoptive transfer of CD8 T cells into a C57BL/6 mouse melanoma model, we demonstrate the requirement for vitamin B6-dependent enzyme activity in mediating effective anti-tumor responses. Our findings show that vitamin B6 metabolism is required for CD8+ T cell proliferation and effector differentiation in vitro and in vivo. Targeting vitamin B6 metabolism may therefore serve as an immunodulatory strategy to improve anti-tumor immunotherapy.